The Impact of Social Media And Mobile Apps on Ecotourism Behavior in The New Normal Era: The Mediating Role of Destination Image - Nurhandini Nurhandini; Widhy Tri Triastuti; Yuni Istanto (PT. Publikasiku Academic Solution, 2023)
The objectives of this study were: 1) To test and influence social media on ecotourism behavior; 2) To test and analyze the effect of mobile applications on ecotourism behavior; 3) To examine the effect of social media on ecotourism behavior with destination image as a mediating variable; and 4) To examine the effect of mobile applications on ecotourism behavior with destination image as a mediating variable. The sample in this study were some tourists at Tebing Breksi Ecotourism Village, Sleman Regency, Yogyakarta Special Region, totaling 286 respondents. The analysis method used in this research is Partial Least Square (PLS). This study proves that Social Media has a significant positive relationship to Ecotourism Behavior; Mobile Applications have a significant positive relationship to Ecotourism Behavior; Social Media has a significant positive relationship to Ecotourism Behavior through Destination Image; Mobile Applications have a significant positive relationship to Ecotourism Behavior through Destination Image.